Analysis of the Effects of FED’s Monetary Policies on Inflation in the USA After the 2008 Global Crisis Through Co-integration and Causality Tests - Saltuk Ağıralioğlu (İktisat Politikası Araştırmaları Dergisi)
In recent years, high inflation has emerged as a common fundamental problem for many countries. Studies investigating the causes of inflation have increased due to the high inflation observed worldwide following the 2008 Global Financial Crisis and the COVID-19 pandemic. Parallel to this, there has been a growing interest in research examining the effects of monetary policies on inflation. This study analyzes the short- and long-term impacts of the Federal Reserve’s (FED) monetary policies on inflation in the United States through co-integration and causality tests. In particular, asset purchases and sales initiated after the 2008 Global Financial Crisis, as interest rate changes failed to produce the desired effects, have provided opportunities to better analyse the impacts of monetary policies. In this research, the period from January 2008 to August 2024, including the COVID-19 era, was examined to determine whether changes in the FED’s balance sheet, the industrial production index, the unemployment rate, and inflation were statistically significant. In this research, based on the results of cointegration, FMOLS, DOLS analysis, and causality tests, increases in the balance sheet were found to have a statistically significant impact on inflation in both the short and long term. Additionally, causality tests revealed that changes in the FED’s balance sheet are a Granger cause of inflation. In the long term, inflation, changes in the balance sheet size, and the industrial production index were identified as causes of changes in unemployment. This finding highlights the importance of central bank balance sheet sizes and the monetary policies influencing these sizes.